Transition to adult care in sleep medicine. (February 2020) - Lu, Mimi; Yee, Brendon J.; Fitzgerald, Dominic A.
Abstract: More children with chronic and complex care needs are transitioned to adulthood due to advancements in medical technology including the use of non-invasive ventilation [NIV] at home and innovative medical therapies. Sleep medicine is becoming a common and at times vital component of the management plan. Various challenges are experienced in transitioning sleep patients depending on the underlying condition. These include the direct conflict between the desires of a young person for independence and their declining ability to provide self-care in neuromuscular patients, the behavioural challenges inherent in the management of children with various syndromes and the funding of equipment, care needs and multidisciplinary team input in an already resource limited adult setting. These patients should be transitioned in an early and coordinated approach following core principles of transition. Ongoing advocacy is required to raise awareness of the increased trend for technology supported young people being transitioned. Further research is required to track and assess the transition process in patients with various sleep conditions.